2006
DOI: 10.1152/ajpheart.00990.2005
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated impairment in vasorelaxation to fluid shear stress in the female vasculature is improved by TNF-α antagonism

Abstract: Arenas, Ivan A., Yi Xu, and Sandra T. Davidge. Age-associated impairment in vasorelaxation to fluid shear stress in the female vasculature is improved by TNF-␣ antagonism. Am J Physiol Heart Circ Physiol 290: H1259 -H1263, 2006. First published November 11, 2005 doi:10.1152/ajpheart.00990.2005.-Aging is associated with alterations in vascular homeostasis, including a reduction in flow-mediated vasodilation, which in women is related to the onset of menopause. We previously found that in female animals, aging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…19,36,37 Recent studies also showed that in ovariectomized 12-to 15-month-old female Sprague-Dawley rats administration of etanercept (0.3 mg/kg, for 4 weeks) also improved endothelium-dependent vascular relaxations and decreased expression of the gp91 phox NAD(P)H oxidase subunits. 28,38 There are also studies showing that anti-TNF-␣ treatment with infliximab improves endothelial dysfunction in humans with vascular inflammation characterized by an up-regulation of TNF-␣. 23 We believe that these findings support the view that anti-TNF-␣ therapy, alone or in combination with standard treatments, may exert vasculoprotective effects in elderly humans.…”
Section: Discussionmentioning
confidence: 99%
“…19,36,37 Recent studies also showed that in ovariectomized 12-to 15-month-old female Sprague-Dawley rats administration of etanercept (0.3 mg/kg, for 4 weeks) also improved endothelium-dependent vascular relaxations and decreased expression of the gp91 phox NAD(P)H oxidase subunits. 28,38 There are also studies showing that anti-TNF-␣ treatment with infliximab improves endothelial dysfunction in humans with vascular inflammation characterized by an up-regulation of TNF-␣. 23 We believe that these findings support the view that anti-TNF-␣ therapy, alone or in combination with standard treatments, may exert vasculoprotective effects in elderly humans.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory factors include, tumor necrosis factor (TNF)-α, IL-6, and IL-1β, which are associated with increased risk of developing VCID (Zuliani et al, 2007). High levels of pro-inflammatory factors contribute to a pro-inflammatory microenvironment, which facilitates vascular dysfunction and promotes endothelial apoptosis, mainly through activation of NF-κB (Arenas et al, 2006; Donato et al, 2008; Donato et al, 2007; Ungvari et al, 2007; Zou et al, 2006). …”
Section: Cerebrovascular Biology and Agingmentioning
confidence: 99%
“…TNF-␣ has been shown to reduce NO bioavailability by decreasing eNOS expression or by increasing NO inactivation through stimulation of NADPH oxidase. Moreover, upregulation of TNF-␣ levels with aging is associated with a decrease in flow-mediated vasodilation leading to higher levels of shear stress (14).…”
Section: E Role Of No In the Phenotypic Adaptation Of Endothelial Cementioning
confidence: 99%